Pena de prisão: reflexões ético-filosóficas sobre a teoria dos fins da pena, alternativas e os princípios limitadores da intervenção punitiva do Estado - Pêcego, Antonio José Franco de Souza (2021)
This dissertation seeks to enable the realization of an ethical-philosophical look at punishment, a controversial and ancient theme, but always current, which has, over time, led to heated debates, justifications and explanations about the ends of the prison sentence. We do not seek to make a historical digression of the penalty because this research is not intended to produce at the end another manual on the penalty of imprisonment as a punishment, the one that before the Enlightenment focused on mutilation, beheading, quartering, hanging and burning in the square public. For a better understanding of the meaning of the prison sentence, as a punishment, we tried to stipulate and work from the dividing point of what came to be characterized as the humanization of sentences that is marked by anthropocentrism. We walk for Positive Law in the via crucis of the theories of the ends of the sentence that concern to what and why to punish. These theories have been built after man became the center of the universe, so that, under a critical eye, we can develop a better understanding and understandingof the doctrines of justification of the penalty. With this, we treat the limiting principles of state intervention and the prison sentence as punishment to better find answers to how to punish, in order to allow the construction of an ethical-philosophical discourse that removes the Kantian objection that no person can be used as a means, after all, as Luigi Ferrajoli rightly warns, the only thing we can expect from prison is that it be the least repressive and desocializing possible. The State's right to punish must have answers to the preceding questions: Why punish? For what punish? How to punish ?. We seek to investigate what makes just or justifiable, morally and / or politically acceptable, which adds to the illegal violence of the offense to the legal punishment as punishment. Also investigate the internal and external justifications of the penalty, as well as philosophically investigate the various epistemological statutes of the problems expressed through the basic question of how to punish, after all, as Luigi Ferrajoli emphasizes, the problem of justification of the penalty is classic, par excellence, of the philosophy of law.